Electrochemical performance of a coaxial fiber-shaped asymmetric supercapacitor based on nanostructured MnO2/CNT-web paper and Fe2O3/carbon fiber electrodes. (August 2018) - Patil, Bebi; Ahn, Suhyun; Yu, Seongil; Song, Hyeonjun; Jeong, Youngjin; Kim, Ju Hwan; Ahn, Heejoon
Abstract: The fiber-shaped supercapacitor is a promising energy storage device in wearable and portable electronics because of its high flexibility, small size, and light weight. However, most of the reported fiber-shaped supercapacitors have exhibited low capacitance and energy density due to the limited surface area between the two fiber electrodes and operating voltage range. Herein, we successfully developed a coaxial fiber-shaped asymmetric supercapacitor (CFASC) made from MnO2 /CNT-web paper as a cathode coupled with Fe2 O3 /carbon fiber as an anode with a high operating voltage of 2.2 V. The prepared CFASC device showed a high volumetric energy density of 0.43 mWh cm −3 at a power density of 0.02 W cm −3, which is comparable to those of previously reported fiber-shaped supercapacitors. Additionally, CFASC exhibited good rate capability, long cycle life, and high volumetric capacitance (0.67 F cm −3 ) with excellent flexibility. The promising performance of CFASC illustrated its potential for portable and wearable energy storage devices. Graphical abstract: The coaxial fiber-shaped asymmetric supercapacitor (CFASC) was successfully developed by simply wrapping the Fe2 O3 /CFs negative electrode with the PVA-LiClO4 gel electrolyte-coated MnO2 /CNT-web paper positive electrode. This CFASC can be operated at large potential windows up to 2.2 V, resulting in high specific energy, and showed excellent cycling stability and device flexibility. Image 1